2015
DOI: 10.1097/mph.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

HLA Polymorphism in Algerian Children With Lymphomas

Abstract: These results indicate that HLA-B*18, DRB1*03, *07, and DQB1*02 may contribute to lymphoma susceptibility, whereas HLA-DRB1*13 and DQB1*03 may confer protection to lymphoma in the Algerian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Other studies on lymphoma include: (1) the role of TP73 and FOXP3 in the pathogenesis of reactive lymphoid hyperplasia and diffuse B-cell lymphoma, as well as the contribution of HLA-G polymorphism to non-Hodgkin lymphoma in Egypt ( 398 400 ), (2) susceptibility of individuals with A/A genotype of TNF promoter (-308A/G) to non-Hodgkins lymphoma in Tunisia ( 401 ) and Egypt ( 402 ) and the identification of HLA-B*18 , DRB1*03 , DRB1*07 , and DQB1*02 as lymphoma susceptibility loci in Algerian children ( 403 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on lymphoma include: (1) the role of TP73 and FOXP3 in the pathogenesis of reactive lymphoid hyperplasia and diffuse B-cell lymphoma, as well as the contribution of HLA-G polymorphism to non-Hodgkin lymphoma in Egypt ( 398 400 ), (2) susceptibility of individuals with A/A genotype of TNF promoter (-308A/G) to non-Hodgkins lymphoma in Tunisia ( 401 ) and Egypt ( 402 ) and the identification of HLA-B*18 , DRB1*03 , DRB1*07 , and DQB1*02 as lymphoma susceptibility loci in Algerian children ( 403 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both CTL and CD4+ T‐cells that recognize HLA class I and class II, respectively, are involved in an antitumor immune response against EBV 62 . Of note, HLA class I region polymorphism is known to have consistent susceptibility effects on sporadic and familial EBV‐positive childhood and adult HL across different geographical locations 63‐69 . The classic case study of familial HL demonstrated that clustering of EBV and certain identical HLA genotypes in pediatric patients with HL can occur in a single‐family 66 in which three siblings were diagnosed with EBV‐positive HL had different HLA class I phenotype from their two unaffected siblings.…”
Section: Tme Modulatorsmentioning
confidence: 99%
“… 62 Of note, HLA class I region polymorphism is known to have consistent susceptibility effects on sporadic and familial EBV‐positive childhood and adult HL across different geographical locations. 63 , 64 , 65 , 66 , 67 , 68 , 69 The classic case study of familial HL demonstrated that clustering of EBV and certain identical HLA genotypes in pediatric patients with HL can occur in a single‐family 66 in which three siblings were diagnosed with EBV‐positive HL had different HLA class I phenotype from their two unaffected siblings. These studies suggest that the antigenic presentation of EBV‐derived peptides is involved in the development of HL (Figure 2 ).…”
Section: Tme Modulatorsmentioning
confidence: 99%
“…In the case of mycosis fungoides and Sezary syndrome, this protective association was mentioned by Jackow et al [ 27 ], who identified HLA-DR6 (*1301, *1302, and *1402) but unfortunately, the association did not remain valid after the correction of p . Another study conducted by Galleze et al [ 64 ] mentioned HLA-DRB1*13 and HLA-DQB1*03 for their protective effect against Hodgkin lymphoma and non-Hodgkin lymphoma.…”
Section: Discussionmentioning
confidence: 99%